Distributed paging and registration in wireless networks. - Das, S. (IEEE Network : the magazine of global information exchange)
The success of current and future wireless networks depends on their ability to provide connections to mobile terminals anywhere and at any time. It is therefore of crucial importance that wireless networks are able to quickly and efficiently locate mobile users at the time of an incoming call, which is achieved in current networks through a combination of paging and registration. In this article we present novel distributed paging and registration procedures that are naturally suited to future distributed wireless network architectures. In addition, the distributed nature of these strategies allows us to effectively balance the paging and registration traffic and the required signal processing throughout the network and alleviate any potential overloads of individual base stations.